Jawara Banten the Social Transformation of Local Elites Muslim in Indonesia - Amiruddin, Suwaib; Irfani, Fahmi (Opción, 2019)
This article discusses the significant changaes of social transformation to- wards one of the local elite Muslim in Indonesia, that elite called asJawara Banten (Strongman) in the province of Banten. During its process,Jawara Banten experienced a vertical mobilization in both social and economic as- pecs. The roles of Jawara was no longer as Jaro, spiritual teachers or Kyai .In Orde Baru and reformation era many of Jawara became entrepreneur, official workers and politicians.Jawara which used to be an Informal Leader trans- formed to be more modern in its role without leaving their identity.The identi- ty and Jawara’s culture themselves were called as Subculture of Violence, the violence culture itself has been the culture of Jawara Banten.Violence used as a tool to gain their position and get a higher social status to be the most respec- ful Jawara in their community.